2019
DOI: 10.1093/pa/gsz040
|View full text |Cite
|
Sign up to set email alerts
|

Select Committees: Understanding and Regulating the Emergence of the ‘Topical Inquiry’

Abstract: Reforms to departmental select committees have enhanced their authority and independence within the House of Commons. Some committees have used this enhanced profile to investigate the actions of specific individuals or private corporations or organisations. Typically, this is in response to media reports that allege some form of wrongdoing. As the standing orders of the House of Commons empower committees to scrutinise government departments and agencies, this is a departure from established practices. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The origin of SO.152 was when the Select Committee on Procedure (1978, para 5.7) reported that there was a 'strong desire' for a more effective means of scrutinising 'the expenditure, administration and policy of government departments' . The provisions of SO.152 give select committee's broad powers which can lead to controversy as outlined by Prescott (2019). In the main, these relate to the immunity of select committees to 'make potentially damaging findings about private individuals or firms without risk of legal reprisals ' (p. 897).…”
Section: Select Committeesmentioning
confidence: 99%
“…The origin of SO.152 was when the Select Committee on Procedure (1978, para 5.7) reported that there was a 'strong desire' for a more effective means of scrutinising 'the expenditure, administration and policy of government departments' . The provisions of SO.152 give select committee's broad powers which can lead to controversy as outlined by Prescott (2019). In the main, these relate to the immunity of select committees to 'make potentially damaging findings about private individuals or firms without risk of legal reprisals ' (p. 897).…”
Section: Select Committeesmentioning
confidence: 99%